Efficacy of ultrasonic activation of NaOCl and orange oil in removing filling material from mesial canals of mandibular molars with and without isthmus - Mirela Sangoi BARRETO; Ricardo Abreu da ROSA; Manuela Favarin SANTINI; Bruno Cavalini CAVENAGO; Marco Antônio Húngaro DUARTE; Carlos Alexandre Souza BIER; Marcos Vinícius Reis SÓ (Journal of Applied Oral Science, 2015)
Objectives The aim of this study was to evaluate the volume of remaining filling material after passive ultrasonic irrigation (PUI) of sodium hypochlorite (NaOCl) and orange oil in mesial canals of mandibular molars, with and without isthmus. Material and Methods Thirty mesial roots of mandibular molars were divided according to the presence or absence of isthmus. Canals were prepared and filled (Micro-CT #1). Filling was removed using rotary instruments, and specimens were sub-divided into three groups according to the irrigation procedures: Conventional – conventional irrigation with NaOCl, PUI/NaOCl – PUI of NaOCl (three activations, 20 seconds each), and PUI/orange oil – PUI of orange oil (Micro-CT#2). Specimens were enlarged using the X2 and X3 ProTaper Next instruments and submitted to the same irrigation protocols (Micro-CT #3). Results No differences were found between the experimental groups in each stage of assessment (P>0.05). The volume of residual filling material was similar to that in Micro-CT #2 and Micro-CT #3, but lower than that observed in Micro-CT #1 (P<0.05). When groups were pooled according to the presence or absence of an isthmus, volume of residual filling material was higher in specimens presenting isthmus (P<0.05). Conclusions PUI of NaOCl or orange oil did not improve filling removal. Isthmus consists in an anatomical obstacle that impairs the removal of filling material.